Interoperable Enterprise Content Management Services - Gürleyen, Safa Burak (Information World, 2014)
This study intended towards rational and understandable development on the field of aplication of the interoperability and enterprise content management (ECM) rules and standarts; on the purpose of creating user satisfaction and providing integrated public services. Turkey’s the Interoperability Rules Guide, which is the standart of interoperability and ECM, European Union’s Frameworks compared with Content Management Interoperability Services (CMIS) Specification , which is created by ECM sectors’ leader organisations, so inadequate and further development aspects have been ascertained. Especially, requirements for components’ identification, execution of storage services at data modeling area and keep tracking current developments of information technologies at configuring connection have been determined and leveragable solutions has been proposed.
Keywords: Interoperability; Enterprise content management; CMIS; ECM